Transcriptome and metabolome analyses reveal that Bacillus subtilis BS-Z15 lipopeptides mycosubtilin homologue mediates plant defense responses - Yang, Qilin; Zhang, Hui; You, Jia; Yang, Jun; Zhang, Qi; Zhao, Jinjin; Aimaier, Reyihanguli; Zhang, Jingbo; Han, Shengcheng; Zhao, Heping; Zhao, Huixin (Frontiers in Plant Science, 2023)
Microbial-plant interactions protect plants from external stimuli, releasing various excitons of their own that activate the plant's defense response and regulate its growth. B. subtilis BS-Z15 was screened from cotton inter-rhizosphere soil, antagonized various plant pathogens, and protected cotton against Verticillium dahliae. This study showed that the BS-Z15 lipopeptide mycosubtilin homologue could act as an exciter to induce systemic resistance (ISR) in plants. Mycosubtilin homologue induced ROS burst and deposition, callose deposition, MAPK (MPK3/MPK6) cascade phosphorylation, and up-regulated PR1 and PDF1.2 gene expression in Arabidopsis seedlings, moreover enhanced resistance of Arabidopsis to Pseudomonas syringae pv. Tomato DC3000 (Pst DC3000) and V. dahliae. The effects of mycosubtilin homologue on the control of plant gene expression were then investigated using transcriptome analysis, which revealed that mycosubtilin homologues triggered Arabidopsis ISR on genes in metabolic pathways like Arabidopsis plant-pathogen interactions, phenylpropanoid biosynthesis, MAPK signaling pathway, and phytohormone signaling. These analyses revealed that mycosubtilin homologues mediate the regulation of plant systemic resistance and growth and development by affecting related metabolites in glycolysis and gluconeogenesis, pentose phosphate pathway pathways, tricarboxylic acid cycle, and amino acid metabolism in Arabidopsis. These findings confirmed that a mycosubtilin homologue could trigger the initiation of the Arabidopsis ISR by interacting with a variety of PTI components and transcriptional metabolic signaling pathways.